The Galactic sky through H.E.S.S. eyes - Sushch, I. (Advances in Astronomy and Space Physics, 2015)
The High Energy Stereosopic System (H.E.S.S.) is an array of five imaging atmospheric Cherenkov telescopes. Since 2003 it has been operating in the configuration of four 12 m telescopes complemented in 2012 by a much bigger 28 m telescope in the centre of the array. It is designed to detect very high energy (VHE) gamma-rays in the range of ∼ 20 GeV to ∼ 50 TeV. Over the past decade it performed extremely sucessful observations of the Galactic plane, which led to the discovery of about 70 sources amongst which the most numerous classes are pulsar wind nebulae, supernova remnants and binary systems. Recently H.E.S.S. also discovered the VHE emission from the Vela pulsar, which became the second pulsar detected at TeV energies after the Crab pulsar. An overview of
the main H.E.S.S. discoveries in our Galaxy and their implications on the understanding of physical processes is discussed in this paper.